More haste less speed: Cognition, creativity, and culture in temporal paradox. (November 2019) - Pagán Cánovas, Cristóbal
The understanding of time in spatial terms ("The hour is approaching") has become the most studied case of conceptual projection in the cognitive sciences. However, the predominant models of direct transfer from the concrete to the abstract, from space to time, do not account even for many conventional meanings, such as the subjective value of speed ("The hour is approaching fast"). Poetic examples such as Ende's Momo, where fast and slow are reversed in a meaningful paradox, show the need for a network model based on blending. The network model of blending theory can provide crucial insights into the goal-driven processes for the mapping and integration of concepts, into the complex nature of the templates connecting mental structures, and into the relation between cultural-cognitive patterns, creativity, and context. For this, it is necessary to focus not only on the cognitive operations of mapping and blending but also on the templates that arise from them and on the know-how that comes with these templates, which are always geared toward purposeful usage in context. Time is very often not time itself, but what we want to make of it. In the ways in which we integrate it with emotions, intentions, and social or cultural background we can find precious keys to understand not only time concepts but also imagination and thought in general.